Genetic Characterization of Clinical Acanthamoeba Isolates from Japan using Nuclear and Mitochondrial Small Subunit Ribosomal RNA - Rahman, Md Moshiur (The Korean Society for Parasitology and Tropical Medicine, 2013)
Because of an increased number of Acanthamoeba keratitis (AK) along with associated disease burdens, medical professionals have become more aware of this pathogen in recent years. In this study, by analyzing both the nuclear 18S small subunit ribosomal RNA (18S rRNA) and mitochondrial 16S rRNA gene loci, 27 clinical Acanthamoeba strains that caused AK in Japan were classified into 3 genotypes, T3 (3 strains), T4 (23 strains), and T5 (one strain). Most haplotypes were identical to the reference haplotypes reported from all over the world, and thus no specificity of the haplotype distribution in Japan was found. The T4 sub-genotype analysis using the 16S rRNA gene locus also revealed a clear sub-conformation within the T4 cluster, and lead to the recognition of a new sub-genotype T4i, in addition to the previously reported sub-genotypes T4a-T4h. Furthermore, 9 out of 23 strains in the T4 genotype were identified to a specific haplotype (AF479533), which seems to be a causal haplotype of AK. While heterozygous nuclear haplotypes were observed from 2 strains, the mitochondrial haplotypes were homozygous as T4 genotype in the both strains, and suggested a possibility of nuclear hybridization (mating reproduction) between different strains in Acanthamoeba. The nuclear 18S rRNA gene and mitochondrial 16S rRNA gene loci of Acanthamoeba spp. possess different unique characteristics usable for the genotyping analyses, and those specific features could contribute to the establishment of molecular taxonomy for the species complex of Acanthamoeba.